High cutaneous amphiregulin expression predicts fatal acute graft‐versus‐host disease. (13th March 2022) - Schultz, Brittney; Miller, Daniel D.; DeFor, Todd; Blazar, Bruce R.; Panoskaltsis‐Mortari, Angela; Betts, Brian C.; MacMillan, Margaret L.; Weisdorf, Daniel J.; Holtan, Shernan G.
Abstract: Background: Amphiregulin (AREG) is increased in circulation in acute graft‐versus‐host disease (aGVHD) and is associated with poor steroid response and lower survival. The expression of AREG in aGVHD target organs and its association with clinical outcomes are unknown. Methods: We performed AREG immunohistochemical staining on skin specimens from 67 patients with aGVHD between the years 2010 and 2015. Two blinded reviewers assessed AREG expression and scored specimens with a semiquantitative scale ranging from 0 (absent) to 4 (most intense). Results: Median AREG score of aGVHD cases was 3. Sixteen of 67 (23.9%) aGVHD cases had an AREG >3. High skin AREG expression (>3 vs. ≤3) was associated with increased overall clinical grade of aGVHD (52.9% vs. 33.4% clinical grade III‐IV, p  = 0.02), reduced 3‐year overall survival (OS; 13% vs. 61%, p  < 0.01), and increased 3‐year non‐relapse mortality (NRM; 56% vs. 20%, p  = 0.05). Conclusion: High skin AREG immunohistochemical expression is associated with high clinical grade aGVHD, poor OS, and increased NRM.